IMPOSTOR PHENOMENON PADA GENERASI Z: TINJAUAN LITERATUR DALAM PERSPEKTIF BIMBINGAN DAN KONSELING - Ike Nurhidayah; Risma Anita Puriani (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the impostor phenomenon in Generation Z and its implications for guidance and counseling. The method used is a systematic literature review by analyzing 21 relevant scientific articles published between 2021 and 2026. The results show that the impostor phenomenon is relatively high among Generation Z and is associated with low self-efficacy, self-esteem, and resilience. This condition contributes to increased anxiety, stress, and obstacles in academic and career development. From a guidance and counseling perspective, this phenomenon can be addressed through services such as individual counseling, group guidance, and cognitive restructuring techniques to help modify negative thought patterns. Therefore, an active role of counselors is needed to help individuals build self-confidence and better understand their potential.